Penggunaan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) Dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Islam - Fathus Saadah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine the improvement of student learning outcomes in learning Islamic Religious Education class VI using cooperative learning model Type Student Teams Achievement Division (STAD) on the material in SD Negeri 42 Lubuklingga academic year 2014/2015. This type of research includes action research research. The subject of this research is the students of class VI SD Negeri 25 Lubuklinggau academic year 2014/2015. The results of this study indicate: through the results of classroom action research on SD Negeri 25 Lubuklinggau an increase. In the first cycle, the level of mastery only amounted to 58.54%. In cycle II the level of mastery increased to 87.80%. Means there is an increase in student learning outcomes and learning activities of the learners after classroom action research. Thus, it can be concluded that there is a significant improvement in learning outcomes before and after classroom action using cooperative learning model Type Student Teams Achievement Division (STAD) in grade 6 students of SD Negeri 25 Lubuklinggau in student learning outcomes. So this research is considered to work well. Keywords: Cooperative Learning Model, Student Learning Outcomes